2019
DOI: 10.3390/ijms20163940
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Biochemical Basis of the Differential Efficacy of First and Second Generation Somatostatin Receptor Ligands in Neuroendocrine Neoplasms

Abstract: Endogenous somatostatin shows anti-secretory effects in both physiological and pathological settings, as well as inhibitory activity on cell growth. Since somatostatin is not suitable for clinical practice, researchers developed synthetic somatostatin receptor ligands (SRLs) to overcome this limitation. Currently, SRLs represent pivotal tools in the treatment algorithm of neuroendocrine tumors (NETs). Octreotide and lanreotide are the first-generation SRLs developed and show a preferential binding affinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 208 publications
(302 reference statements)
1
42
0
Order By: Relevance
“…These latest results strengthen our observations on the effect of OCT, PAS and their combination on GH secretion in somatotroph tumor primary cultures. Indeed, the cAMP pathway and the regulation of ion conductance to prevent [Ca 2+ ] i increase are crucial biological mechanisms involved in the antisecretory activity exerted by SRLs in somatotroph tumors [ 7 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These latest results strengthen our observations on the effect of OCT, PAS and their combination on GH secretion in somatotroph tumor primary cultures. Indeed, the cAMP pathway and the regulation of ion conductance to prevent [Ca 2+ ] i increase are crucial biological mechanisms involved in the antisecretory activity exerted by SRLs in somatotroph tumors [ 7 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…First-generation somatostatin receptor ligands (fg-SRLs), octreotide (OCT) and lanreotide (LAN), still represent the first choice as medical treatment in acromegaly patients [ 2 , 5 , 6 ]. Both OCT and LAN are stable octapeptides showing a preferential binding affinity for the somatostatin receptor subtype 2 (SST 2 ), widely expressed in GH-secreting pituitary tumor cells [ 7 , 8 ]. In this context, a number of studies already demonstrated a positive correlation between SST 2 expression in GH-secreting tumor cells and fg-SRL efficacy in reducing hormone secretion both in vitro and in vivo [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Octreotide and lanreotide are the first-generation SSAs and show a high binding affinity to SSR2 and 5, while pasireotide, which is a second-generation SSA, has high affinity for multiple SSRs (SSR5 > SSR2 > SSR3 > SSR1) (15). Lanreotide, in details, is currently approved for treatment of NETs and has a relevant cytostatic and antisecretive effect.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although cytotoxic drugs are scarcely effective on PASCs, as expected in putative CSCs, these cells express SSTRs and D2R and are responsive to the respective agonists. Considering that the clinically approved receptor agonists, such as octreotide, lanreotide, pasireotide, and cabergoline, display both anti-secretory and, although less defined, antiproliferative activities (133), it is conceivable that these dual effects may involve the modulation of receptors in different PA cell subsets: the former likely mainly acting on differentiated cells, and the latter on PASCs. Further studies trying to clarify this issue are most warranted.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%